The Accident in Being - John W P Phillips (Media Theory, 2021)
Michel Serres’s work traces a historical transition where technologies of mediation replace a framework of life formerly managed by an economics of production. Readings of Serres tend to affirm in this transition the opening to an ecology (econarratology or media-ecology) or towards a replacement of the human in trans- or post-humanism. In this article I analyse the terms of the transition in Serres’s affirmation of a philosophy grounded in the potential for connection between the traditions of storytelling and the sciences of connection. The article rediscovers within his overt Hellenism a figure of the Anthropos affirmed in the Sophist philosophies that Plato had set out to destroy. If science proceeds, first in its Hellenic dawn, and more recently in seventeenth century arithmetic, then it must be disabused of its war-game attitude. Serres affirms science (almost singularly) as the condition on which the species might continue its adventure into the future, and in the process he establishes a position that may challenge ecologically oriented discourses.